2003
DOI: 10.1118/1.1584040
|View full text |Cite
|
Sign up to set email alerts
|

Compensator quality control with an amorphous silicon EPID

Abstract: The calibration and quality control of compensators is conventionally performed with an ion chamber in a water-equivalent phantom. In our center, the compensator factor and four off-axis fluence ratios are measured to verify the central axis beam modulation and orientation of the compensator. Here we report the investigation of an alternative technique for compensator quality control using an amorphous silicon electronic portal imaging device (a-Si EPID). Preliminary experiments were performed to identify appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The linearity of the Varian aS500 EPID with increasing MU setting at central axis has been examined by a number of authors. [3][4][5] The linearity of a newer dosimetric mode that does not exhibit frame loss and acquires extra frames following beam-off to ensure that the final frame is completely read out was examined by van Esch et al 6 They found that the detector had a linear curve for doses from 2 to 300 MU; however, differences below 30 MU were found due to signal rounding. The linearity of the Elekta iView EPID has been examined by McDermott et al 7 and more recently Winkler et al 8 They reported that the reduction in EPID signal for low doses ͑Ͻ15 MU͒ was due to a dose rate or dose per frame response.…”
Section: Introductionmentioning
confidence: 99%
“…The linearity of the Varian aS500 EPID with increasing MU setting at central axis has been examined by a number of authors. [3][4][5] The linearity of a newer dosimetric mode that does not exhibit frame loss and acquires extra frames following beam-off to ensure that the final frame is completely read out was examined by van Esch et al 6 They found that the detector had a linear curve for doses from 2 to 300 MU; however, differences below 30 MU were found due to signal rounding. The linearity of the Elekta iView EPID has been examined by McDermott et al 7 and more recently Winkler et al 8 They reported that the reduction in EPID signal for low doses ͑Ͻ15 MU͒ was due to a dose rate or dose per frame response.…”
Section: Introductionmentioning
confidence: 99%
“…1 As the image is instantly obtained, there is no need to process a film and therefore it is possible to verify the accuracy of positioning during the course of the field delivery. As the technology develops, EPIDs are not only used for patient positioning verification but also for a variety of other applications: linac quality assurance ͑QA͒, [2][3][4] compensator design and verification, 5,6 and patient dosimetry. [7][8][9][10][11][12][13][14][15][16][17][18] This is of special interest for intensity modulated radiation treatments ͑IMRT͒.…”
Section: Introductionmentioning
confidence: 99%
“…31,41 For the a-Si EPIDs of another vendor, a variation in response of 0.8% (1 SD) over a period of 1 month has been reported16, and a drift depending on the beam quality up to 4% over a period of 5 months. 82 …”
Section: Discussionmentioning
confidence: 99%
“…42,43,73,82,122,131 All of these studies used the Varian EPID, which has a different scintillator from the Elekta and Siemens detectors. The EPID signal for these studies was measured over different dose ranges, energies and dose-rate settings compared to measurements with the Elekta EPIDs.…”
Section: Introductionmentioning
confidence: 99%